Listeria monocytogenes dissemination in farming and primary production: Sources, shedding and control measures. (February 2021) - Rodriguez, C.; Taminiau, B.; García-Fuentes, E.; Daube, G.; Korsak, N.
Abstract: Listeria monocytogenes ( L. monocytogenes ) is a well-known pathogenic bacterium that causes the disease listeriosis in both humans and animals. Human transmission mainly occurs via ingestion of contaminated foods and specifically affects pregnant women, newborns, elderly individuals and immunosuppressed individuals. Several outbreaks have been historically associated with the consumption of fresh raw milk and unpasteurized cheese, highlighting the role of good farm hygiene measures to reduce the probability of milk contamination. L monocytogenes is ubiquitous in the environment, and therefore, this bacterium is commonly found in silage, haylage, grazing pastures, crop fields, farmyards and even water. Faeces of wild animals, including gulls and rooks, have also been described as important vectors of the pathogen for farm animal contamination, as well as animal bedding, soils or feed bunk tanks, especially when animals are housed during indoor months. Milking lines, including filters, collectors, bulk tanks and other utensils in the room, have been described as important sites of bacterial detection. The ability of L. monocytogenes to produce biofilms and to survive in humid environments makes elimination difficult and increases its persistence in equipment and on floors, leading to high risk of milk contamination at harvest in farms. This review explores in depth the different sources of L. monocytogenes contamination described in production farms, with a special focus on ruminants, identifying the transmission vectors and analysing the applicable control measures at each stage. Highlights: Listeriosis is an important infection for humans and animals. L.monocytogenes is ubiquitous in the farm environment. Feedstuffs, water, surfaces and manure are the main bacterial vectors. Control measures include biofilm cell detachment from surfaces. Control measures must be established in the farm and its surroundings at each stage of production.